The role of information sources and characteristics of children in the acceptance of Japanese encephalitis (JE) mass immunization in Bali Province - Nyoman Suardani; Dewa Nyoman Wirawan; Anak Agung Sagung Sawitri (Public Health and Preventive Medicine Archive, 2019)
Background and purpose: Japanese encephalitis (JE) is a public health issue that can be prevented by immunization programs. Indonesia began the JE immunization campaign in Bali through simultaneous immunization for children aged 9 months to 15 years. Although information dissemination has been carried out, knowledge, perceptions and characteristics of mother and child can influence the acceptance and uptake of immunization for children. This study aims to determine the factors that influence acceptance of JE mass immunization in Bali Province. Methods: Secondary data analysis was performed on the results of the JE Supplementary Immunization Activities (SIA) Udayana University survey which consisted of 1,284 mothers and 2,107 children. The survey was conducted from June-August 2018 in nine districts/cities in Bali Province. The association between knowledge, perception and respondents’ characteristics with acceptance of JE mass immunization was analyzed with chi square test and multivariate analysis was conducted using logistic regression. Results: The proportion of children who received immunization was 93.9% (95%CI: 92.8-94.9). The results of the bivariate analysis showed that there was a significant association between acceptance of JE mass immunization with the child’s age, sex, educational status, complete basic immunization history, mother’s perception of severity, benefits, barriers, knowledge and sources of information (p<0.05). Multivariate analysis shows that the variables which significantly increase JE mass immunization acceptance are information from a combination of media and face to face education (AOR=3.95; 95%CI: 2.01-7.77), schooling children (AOR=2.43; 95%CI: 1.23-4.79), living outside of Denpasar City (AOR=2.32; 95%CI: 1.49-3.62), children who have received complete basic immunization (AOR=2.22; 95%CI: 1.42-3.49), face to face information only (AOR=2.11; 95%CI: 1.21-3.70) and girls (AOR=1.68; 95%CI: 1.15-2.46). Conclusion: Information disseminated via a combination of media and face to face is the strongest variable influencing JE mass immunization acceptance. Providing appropriate information through a combination of media and face to face education by health or non-health workers needs to be considered.